Unique action mechanisms of tramadol in global cerebral ischemia-induced mechanical allodynia. Issue 9 (15th June 2016) - Matsuura, Wataru; Kageyama, Erika; Harada, Shinichi; Tokuyama, Shogo
Abstract : Central poststroke pain is associated with specific somatosensory abnormalities, such as neuropathic pain syndrome. Although central poststroke pain is a serious condition, details pertaining to underlying mechanisms are not well established, making current standard treatments only partially effective. Here, we assessed the effects of tramadol, an analgesic drug mediated by opioid receptors, using a mouse model of global cerebral ischemia. Ischemia was induced by bilateral carotid artery occlusion (30 min) in male ddY mice. Development of hind-paw mechanical allodynia was measured 3 days after bilateral carotid artery occlusion using the von Frey test. Mechanical allodynia was significantly and dose dependently suppressed by intraperitoneal tramadol (10 or 20 mg/kg). These effects, which peaked at 10 min and continued for at least 60 min, were inhibited by naloxone (nonselective opioid receptor antagonist, 1 mg/kg, intraperitoneal). Tramadol antinociception was significantly negated by β-funaltrexamine (selective μ-opioid receptor antagonist, 20 mg/kg, intraperitoneal), but not naltrindole (selective δ-opioid receptor antagonist, 5 mg/kg, intraperitoneal) or nor-binaltorphimine (selective κ-opioid receptor antagonist, 10 mg/kg, intraperitoneal) after 5 min, by β-funaltrexamine and nor-binaltorphimine but not naltrindole after 10 min, and by all selective opioid receptor antagonists at 15 and 30 min after tramadol treatment. These results suggested that antinociception induced by tramadol through various opioid receptors was time dependent. Furthermore, it is possible that the opioid receptors involved in tramadol-induced antinociception change over time with the metabolism of this drug.